A study of phase transformation at the surface of a zirconia ceramic - Roberts, O; Lunt, A; Ying, S; Sui, T; Baimpas, N; Dolbnya, I; Parkes, M; Dini, D; Kreynin, S; Neo, T; Korsunsky, A (Newswood Limited, 2014)
Yttria Partially Stabilized Zirconia (YPSZ) is one of the most important engineering ceramic materials in that it displays a whole host of outstanding structural and functional properties. Of particular importance for load-bearing applications is the remarkable fracture toughness of YPSZ that arises from its ability to undergo martensitic transformation, a phase transformation that is dependent on stress, temperature, time, humidity, grain size, and the proximity of an interface. The present study was aimed at revealing the influence of the thermal ageing on the tetragonal to monoclinic phase transformation in the near-surface regions of YPSZ. In order to perform qualitative and quantitative characterisation of the phase composition, three principal microscopic techniques were employed: atomic force microscopy, depth resolved Raman micro-spectroscopy, and synchrotron X-ray diffraction. Satisfactory consistency was achieved between the results obtained using different techniques. Moreover, the data obtained in this way displayed complementarity that provided valuable input for the development of thermodynamic modelling of the complex inter-dependence between phase state and processing history of zirconia ceramics.